2020
DOI: 10.1063/5.0022636
|View full text |Cite
|
Sign up to set email alerts
|

AlScN-based MEMS magnetoelectric sensor

Abstract: MEMS sensors based on magnetoelectric composites have attracted great interest due to their capability to detect weak magnetic fields, showing high potential in applications like biomagnetic field detection and magnetic particle imaging. This paper reports on a scandium aluminum nitride thin film-based MEMS magnetoelectric sensor. The sensor consists of a polycrystalline silicon cantilever with a size of 1000 μm × 200 μm covered by a piezoelectric Al0.73Sc0.27N and a magnetostrictive (Fe90Co10)78Si12B10 thin f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 38 publications
0
42
0
Order By: Relevance
“…A further improvement by a factor of two could be obtained by exciting both electrodes and , phase shifted by 180°. Additionally, alternative piezoelectric materials with larger piezoelectric coefficients, such as AlScN [ 63 , 64 , 65 ] could increase the electrical sensitivity significantly and result in comparable with bending modes.…”
Section: Resultsmentioning
confidence: 99%
“…A further improvement by a factor of two could be obtained by exciting both electrodes and , phase shifted by 180°. Additionally, alternative piezoelectric materials with larger piezoelectric coefficients, such as AlScN [ 63 , 64 , 65 ] could increase the electrical sensitivity significantly and result in comparable with bending modes.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, there has been increasing interest in the influence of the quality factor (Q) on the properties of resonator ME sensors [56,[379][380][381][382]. Different techniques were used to enhance the Q and improve the performance of ME sensors.…”
Section: Magnetic Sensorsmentioning
confidence: 99%
“…For the ME sensors operating in resonance, the SNR increases by Q 1/2 [379,383]; for the ΔE operation scheme, an improvement in the SNR proportional to Q 3/2 can be achieved [384]. By using AlScN with a higher ME voltage coefficient instead of AlN in ME sensors, Su et al successfully fabricated devices with higher Q [382]. In conclusion, there are a lot of factors, including materials, pressure, magnetic fields, electric excitation amplitude and so on, that influence the total performance of ME sensors, giving many paths for further study.…”
Section: Magnetic Sensorsmentioning
confidence: 99%
“…However, these sensors still have too narrow of a bandwidth for use in DBS applications due to the presence of much higher frequencies (stimulation frequency and harmonics). It is reported that ME sensor approaches offer a high potential for this application since the resonance frequency of an ME sensor can be tuned to the stimulation frequency or its higher harmonics to measure the artificial magnetic signal of DBS [ 24 , 25 , 26 ]. However, such resonant, narrow-band ME sensors measure only a single frequency component of the entire broadband DBS signal, therefore, higher sensor sensitivity is required.…”
Section: Introductionmentioning
confidence: 99%